Internalizing Educational Signs and Symbols in Enhancing Diversity and Pancasila Values at SMA Negeri 10 Palembang - Wulandari, Wulandari (LPPM Institut Studi Islam Sunan Doe, 2022)
This research will be conducted to find out how to internalize signs and symbols that can increase diversity and Pancasila values at SMA Negeri 10 Palembang. In conducting this research, researchers used a type of qualitative research method with a descriptive approach by making direct observations at schools. Observational data obtained through direct observation activities. Based on the results of observations that have been made that signs and symbols in schools can increase the morality of students. Diversity as a school symbol is seen in the absence of discrimination and racism from students. Culture at school can shape Pancasila values and its application in the school environment makes students have the characteristics of a Pancasila student profile.